Frequency entrainment in a self-oscillatory system under parametric excitation - Da, Hoang Van; Sy, Nguyen Thac (Vietnam Journal of Mechanics, 2003)
In the present paper, the frequencies for appearing the entrained oscillations in a self-oscillatory system under the parametric excitation, have been determined. The almost periodic oscillation which develops from the entrained oscillation when the driving frequency is given just outside the region of entrainment also have been investigated by the method of the phase plane.